2015
DOI: 10.3233/bmr-140488
|View full text |Cite
|
Sign up to set email alerts
|

Spine radiography in the evaluation of back and neck pain in an orthopaedic emergency clinic

Abstract: Plain radiography of the spine was unnecessary in most patients initially evaluated with non-specific acute back pain and does not improve the clinical outcome. The implementation of national and international guidelines is a slow process, but helps to reduce costs and to protect patients from unnecessary ionizing radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…We found two systematic reviews presented in 5 articles [13][14][15][16][17]. Furthermore, we found 2 narrative reviews [10,18], 7 prospective cohort studies [19][20][21][22][23][24][25][26], 9 retrospective cohort studies often collecting data from medical records [27][28][29][30][31][32][33][34][35], and 8 case reports [36][37][38][39][40][41][42][43]. Six studies provided diagnostic test accuracy data related to red flags for detection of malignancy for patients with LBP and were included in the assessment of diagnostic accuracy using the QUADAS-2 (Table 1) [20,21,22,24,26,29].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found two systematic reviews presented in 5 articles [13][14][15][16][17]. Furthermore, we found 2 narrative reviews [10,18], 7 prospective cohort studies [19][20][21][22][23][24][25][26], 9 retrospective cohort studies often collecting data from medical records [27][28][29][30][31][32][33][34][35], and 8 case reports [36][37][38][39][40][41][42][43]. Six studies provided diagnostic test accuracy data related to red flags for detection of malignancy for patients with LBP and were included in the assessment of diagnostic accuracy using the QUADAS-2 (Table 1) [20,21,22,24,26,29].…”
Section: Search Resultsmentioning
confidence: 99%
“…The prospective primary care cohort studies (4 studies; 4864 participants) reported prevalences of malignancy in patients with LBP between 0% to 0.6 -0.7% [19/20,22,24,25]. Cohorts studies of radiographic reports (3 studies; 2981 participants) from patients referred from primary care reported prevalences between 0.2% and 7.0% [28,31,34]. One retrospective cohort study in tertiary care (n = 1109 participants) found a prevalence of 5.9% [32].…”
Section: Prevalencementioning
confidence: 99%
“…The Spurling test involves turning the patient's head contralateral and ipsilateral to the pain, each time applying gentle downward axial compression. 39,38 A positive results reproduces radicular pain related to constriction of the neural foramen. Shoulder abduction, as recently portrayed above, is characteristic of radicular side effects.…”
Section: Patient Examinationmentioning
confidence: 83%
“…40 In case there is worry for warnings, history of injury, or the patient has bombed moderate medicines following a month and a half, then, at that point plain foremost/back and sidelong radiographs can be requested with the expansion of flexion/extension sees in case there is worry for spinal insecurity. 39 In patients with persistent or progressive neurologic involvement, use an MRI for all cervical spinal conditions. 39,37,41 This is followed by a computed tomography (CT) scan or CT myelogram for patients unable to undergo MRIs, with CT myelography having preference over CT scan if there is concern for neurologic impingement.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation